2020
DOI: 10.18488/journal.62.2020.76.375.386
|View full text |Cite
|
Sign up to set email alerts
|

The Contingent Fit between Management Control System and Capabilities on Sustainability Performance

Abstract: This study aims to analyze the contingent fit between the management control system (MCS) with capabilities to improve the company's sustainability performance. The final sample was 185 environmental managers, human resources, marketing, operational, and corporate social responsibility (CSR) managers from 45 listed companies on the Indonesia Stock Exchange that published the annual report. Primary research data were taken by questionnaire. The data analysis method uses structural equation models with the help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The core of the structural contingency approach model is that organizational effectiveness results from fitting organizational factors, such as organizational systems, to contingencies that reflect an organization's situation (Donaldson 2001). Rosini et al (2020) stated that contingency theory is used to analyze management control system (MCS) contingent fit and capability for performance. Matching the MCS to the firm's capabilities can enhance performance.…”
Section: Contingency Theory Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The core of the structural contingency approach model is that organizational effectiveness results from fitting organizational factors, such as organizational systems, to contingencies that reflect an organization's situation (Donaldson 2001). Rosini et al (2020) stated that contingency theory is used to analyze management control system (MCS) contingent fit and capability for performance. Matching the MCS to the firm's capabilities can enhance performance.…”
Section: Contingency Theory Perspectivementioning
confidence: 99%
“…Consistent with (Hussaini and Muhammed 2018), Pakurár et al (2019) assessed the relationship between IC and financial performance for Jordanian banks and found that IC significantly influenced their financial performance. Rosini et al (2020) found that management control systems directly affect performance.…”
Section: Organizational Performancementioning
confidence: 99%
“…The workforce nowadays is filled with different attitudes. Recently, there has been much support for human capital growth, lifelong learning and a constant focus on soft skill growth (Theriou, Maditinos & Theriou, 2020). Nonetheless, many times, concerns are just attended to at the surface level but not at the roots of the cause.…”
mentioning
confidence: 99%